Large-scale survey of a neglected agent of sparganosis Spirometra erinaceieuropaei (Cestoda: Diphyllobothriidae) in wild frogs in China. - Xi Zhang; Xiu Hong; Shi Nan Liu; Peng Jiang; Shu Chuan Zhao; Chuan Xi Sun; Zhong Quan Wang; Jing Cui (Public Library of Science (PLoS), 2020)
BACKGROUND:In China, frogs play an understudied role in the spread of human sparganosis (caused by the larval form of Spirometra). However, our knowledge about the prevalence of sparganum infection in frogs remains fragmented, and the taxonomic identification of the parasite is still controversial. METHODOLOGY/PRINCIPAL FINDINGS:The prevalence of sparganum infection in wild frogs was surveyed at 145 geographical locations from 28 of the 34 provinces/autonomous regions/municipalities in China for six years. The collected sparganum isolates from the different locations were subjected to molecular identification by a multiplex PCR assay and then were analysed with clustering analysis. In the survey, sparganum infection was found in 8 out of 13 of the collected frog species, and the most frequently infected species was Pelophylax nigromaculatus (the infection rate was up to 14.07%). Infected frogs were found in 80 of the 145 surveyed locations. The sparganum infection rates in the wild frogs in several regions of China were still high (above 10%), especially in South and Southwest China. A total of 72 spargana were selected for molecular identification, and the clustering analysis showed that sequences from the Chinese isolates were very similar to those identified as from Spirometra erinaceieuropaei. However, the taxonomy of the genus remains confused and further analysis is required. CONCLUSIONS:Eating wild frogs is associated with considerable health risks in China. Several traditional Chinese folk remedies may increase the risk of infection. The sparganum isolates in China are most likely from S. erinaceieuropaei, but new studies, especially comprehensive morphological analyses, are needed in the future.